(untitled) (Eurasian Research Bulletin, 2024)
This article presents the analysis of the prospects for production in dekhkan farms of the Kashkadaryа region. It also presents a set of econometric models and forecasts of livestock and crop production indicators in dekhkan farms and household plots. The analysis of foreign economic relations of the agricultural system is presented in tables and diagrams.